2019
DOI: 10.1038/s41598-019-52036-5
|View full text |Cite
|
Sign up to set email alerts
|

Using high-throughput sequencing to explore the anti-inflammatory effects of α-mangostin

Abstract: Lipopolysaccharide (LPS) causes an inflammatory response, and α-mangostin (α-MG) is an ingredient of a Chinese herbal medicine with anti-inflammatory effects. We investigated the mechanism by which α-MG reduces LPS-stimulated IEC-6 cells inflammation. A genome-wide examination of control, LPS-stimulated, and α-MG-pretreated cells was performed with the Illumina Hiseq sequencing platform, and gene expression was verified with quantitative real-time PCR (qPCR). Among the 37,199 genes profiled, 2014 genes were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The concentration and the method of administration of LPS were referred to Yin et al. ( Yin et al., 2019 ). The rats in the LPS group were injected LPS (10 mg/kg) intraperitoneally on day 13.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration and the method of administration of LPS were referred to Yin et al. ( Yin et al., 2019 ). The rats in the LPS group were injected LPS (10 mg/kg) intraperitoneally on day 13.…”
Section: Methodsmentioning
confidence: 99%
“…The rats in the control and PA groups received 20 ml/kg of drinking water and 200 mM PA, respectively, for 14 consecutive days. The concentration and the method of administration of LPS were referred to Yin et al (Yin et al, 2019). The rats in the LPS group were injected LPS (10 mg/kg) intraperitoneally on day 13.…”
Section: Experimental Animals and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study proposed a mechanism by which alpha-mangostin successfully modulated LPS-stimulated IEC-6 cell inflammation using a genome-wide examination of control, LPS-stimulated, and alpha-mangostin-pretreated cells. The study showed that α-MG pretreatment reduced LPS-induced expressions of NLRP3, caspase 1, interleukin (IL)-18, and IL-1β (121).…”
Section: Mangosteenmentioning
confidence: 99%
“…α-mangostin (α-MG) is a herbal medicine isolated from the pericarp of mangosteen fruits that has anti-inflammatory effects [ 76 ]. In a study conducted by Yin et al [ 77 ] its role in a rat model of colitis induced by LPS was evaluated. They showed that administration of α-MG ameliorated LPS-induced intestinal villi detachment, congestion, and hemorrhage.…”
Section: Inhibition Of the Nlrp3 Inflammasome Ameliorates Colitismentioning
confidence: 99%